An Overview on Food Preservation Methods (International Journal of Innovative Research in Computer Science & Technology, 2022)
Food is required for the survival of all living  organisms. Foods include a variety of nutrients such as carbs,  lipids, proteins, vitamins, and minerals. An organism  consumes and digests these nutrients in order to generate  energy, which is needed to promote development and sustain  regular living processes. Food spoilage can be caused by  environmental or food-borne chemical, enzymatic, as well as  occurs when the bacteria. Food has a finite shelf life;  preservative are used in food to enhance that shelf life or  preserve quality; nevertheless, these preservatives may have  certain detrimental side effects. As both a result, today's  consumer demand for minimally processed foods devoid of  chemical preservatives has fueled interest in biology  alternatives. By preventing or inhibiting growth of  microorganisms, processed foods are substances found in  food, pharmacological dosage forms, but rather cosmetic  planning and preparation to maintain product accuracy and  reliability, increase and otherwise preserve nutrient  advantage, maintain edibility but also wholesomeness, start  providing leavening (yeast), control pH, enhance flavour, or  provide colour. A good preservative must be effective at low  levels, non-toxic, generally compatible with all the other  components in the recipe, as well as stable throughout the  shelf life of the recipe. This review article examines the use  of natural food preservatives as an alternative to artificial  preservatives for a better human diet.
Keywords: Bacteria; Drying; Freezing; Protein